2020
DOI: 10.1038/s41598-020-67138-8
|View full text |Cite
|
Sign up to set email alerts
|

Human salivary Raman fingerprint as biomarker for the diagnosis of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disease leading to progressive and irreversible muscle atrophy. The diagnosis of ALS is time-consuming and complex, with the clinical and neurophysiological evaluation accompanied by monitoring of progression and a long procedure for the discrimination of similar neurodegenerative diseases. The delayed diagnosis strongly slows the potential development of adequate therapies and the time frame for a prompt intervention. The discovery of new biomarkers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 74 publications
1
36
0
Order By: Relevance
“…The salivary Raman analysis was carried out following and slightly modifying the analytical protocol developed and validated by our group, leading to the observation of the whole biochemical pattern of saliva 15 . The sample preparation procedure was reduced avoiding the filtration step, making in this way the analysis faster, cheaper and more informative, modifying consecutively the Raman acquisition parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The salivary Raman analysis was carried out following and slightly modifying the analytical protocol developed and validated by our group, leading to the observation of the whole biochemical pattern of saliva 15 . The sample preparation procedure was reduced avoiding the filtration step, making in this way the analysis faster, cheaper and more informative, modifying consecutively the Raman acquisition parameters.…”
Section: Resultsmentioning
confidence: 99%
“…These techniques have already proved their applicability in the diagnosis of infections at the point-of-care, with promising results also for early diagnosis and monitoring of multiple human diseases 14 . Besides the application in cell and tissue analysis for cancer detection, RS has demonstrated its reliability and promising applicability also in the analysis of complex biological samples like saliva for disease detection and monitoring 15 . The use of saliva as substrate for Raman analysis has demonstrated unparalleled advantages related mainly to the limited sample processing required, the negligible invasiveness of sample collection, coupled to the multitude of molecules and disease biomarkers that can be investigated for clinical purposes 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Sample preparation was conducted depositing a 5 ”L drop on a Calcium Fluoride (CaFl 2 ) disk, dried overnight at room temperature. The data processing procedure was performed following and adapting the protocol reported by Carlomagno et al [ 21 ]. Briefly, all the spectra were fit with a third-degree polynomial baseline, considering 68 baseline points, and consecutively normalized by a unit vector.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we observed that the SERS spectra of ALS patients with short‐duration group (≀3 years) were significantly different from long‐duration group (>3 years), and the metabolisms of glucose, amino acid, nucleic acid, and antioxidant were highly correlated with disease progression 8 . Recently, Carlomagno et al also reported that salivary Raman spectra could be a potential biomarker for ALS in a small sample size of late‐stage ALS patients, which provided additional evidence that SERS spectroscopy could be a useful tool for the diagnosis of ALS 9 . For the time being, no study has been reported to compare the plasma SERS spectra between ALS patients and healthy controls, and the ALS‐relevant SERS bands have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, Carlomagno et al also reported that salivary Raman spectra could be a potential biomarker for ALS in a small sample size of late-stage ALS patients, which provided additional evidence that SERS spectroscopy could be a useful tool for the diagnosis of ALS. 9 For the time being, no study has been reported to compare the plasma SERS spectra between ALS patients and healthy controls, and the ALS-relevant SERS bands have not been identified. We analyzed the plasma-nanoparticle complexes-based SERS features in ALS patients and healthy controls, aiming to search for specific SERS markers that could serve as potential indicator of ALS.…”
Section: Introductionmentioning
confidence: 99%